Strategi Pengembangan Pemasaran Usaha Mikro Kecil dan Menengah (UMKM) pada Era Digital di Probolinggo - Badrul Qomar; Muhammad Zakaria Zaka; Devy Habibi Muhammad (Ali Institute of Research and Publication, 2024)
This research discusses marketing development strategies for Micro, Small and Medium Enterprises (MSMEs) in the digital era in BulujaranLor Village, TegalSiwalan District, Probolinggo Regency. The main focus of this research is increasing the use of digital technology, such as social media and e-commerce, to expand the marketing reach of local MSME products, including banana chips, cassava chips and other products. Through training conducted by KKN students, MSMEs are encouraged to adapt to the digital era through the use of online media as an effective marketing tool. The results of this activity show that digital education is able to increase the understanding of MSME actors in utilizing technology for business development. Adequate facility support and participant enthusiasm are supporting factors for the success of this program, although several obstacles such as limited time, funds and public awareness are still faced. In conclusion, digital technology has an important role in advancing MSMEs and improving the local economy in this era of globalization.